Sustainable Modularity Approach to Facilities Development Based on Geothermal Energy Potential - Nataša Ćuković Ignjatović; Ana Vranješ; Dušan Ignjatović; Dejan Milenić; Olivera Krunić (Applied Sciences, 2021)
The study presented in this paper assessed the multidisciplinary approach of geothermal potential in the area of the most southeastern part of the Pannonian basin, focused on resources utilization. This study aims to present a method for the cascade use of geothermal energy as a source of thermal energy for space heating and cooling and as a resource for balneological purposes. Two particular sites were selected—one in a natural environment; the other within a small settlement. Geothermal resources come from different types of reservoirs having different temperatures and chemical compositions. At the first site, a geothermal spring with a temperature of 20.5 °C is considered for heat pump utilization, while at the second site, a geothermal well with a temperature of 54 °C is suitable for direct use. The calculated thermal power, which can be obtained from geothermal energy is in the range of 300 to 950 kW. The development concept was proposed with an architectural design to enable sustainable energy efficient development of wellness and spa/medical facilities that can be supported by local authorities. The resulting energy heating needs for different scenarios were 16–105 kW, which can be met in full by the use of geothermal energy.